MODEL PARTISIPASI MASYARAKAT PINGGIR SUNGAI DALAM PROGRAM PENGELOLAAN LINGKUNGAN PERMUKIMAN BERBASIS KOMUNITAS DI KELURAHAN PAHANDUT SEBERANG KOTA PALANGKA RAYA KALIMANTAN TENGAH - Eti Dewi Nopembereni; - Sugiyanto (Agric, 2017)
Community-based Settlement Management Program (PLPBK) is a Central GovernmentProgram through the Ministry of Public Works, which aims to create a harmonious community life order with a safe, comfortable and healthy living environment, self-sustaining and sustainable, and has high economic value for its citizens. This study aims to 1). Identify programs related to the level of community participation, 2) Analyze community-owned social capital, 3) Analyze community behavior on program activities. Determining the location is “purposively” as the site is a top priority on Community-Based Settlement Environmental Management Program (PLPBK). Random sampling was 30 people. Primary data sources are households and secondary data obtained from BPS and related agencies. The results showed that the level of community participation in PLPBK activities was high (46.41%), the absorption of funds reached 98% and there has been a significant change in community behavior under the PLPBK Program.